Guiding Agricultural Expansion to Spare Tropical Forests. Issue 4 (14th December 2014) - Dinerstein, Eric; Baccini, Alessandro; Anderson, Michael; Fiske, Greg; Wikramanayake, Eric; McLaughlin, David; Powell, George; Olson, David; Joshi, Anup
Abstract Commodity crop expansion in the tropics presents the challenge of preserving tropical moist forest (TMF) ecosystems and their role in carbon sequestration. We propose an algorithm, specific to the TMF biome, which identifies 125 million ha of degraded, low‐carbon density land (LCDL) in the Pantropical TMF belt for agricultural expansion. About 65 million ha of LCDL are in contiguous tracts >5, 000 ha and <500 m elevation, meeting the prerequisites for commercial‐scale oil palm production, the fastest‐expanding industrialized commodity crop in the TMF. These areas could support expansion of commercial agriculture for another 25–50 years without further conversion of TMF. Confining agricultural expansion to the LCDL can avoid the release of approximately 13 billion tons of CO2 while saving valuable tropical biodiversity. The simplicity and transparency of this easily monitored metric could prove useful to producers, governments, investors, environmental stewards, and consumers and enhance good governance in tropical regions.